Efisiensi tata niaga umbi singkong dan umbi kimpul oleh masyarakat sekitar hutan di kabupaten Gunungkidul - Suhartono Suhartono; Ary Widiyanto (Agroindustrial Technology, University of Trunojoyo Madura, 2022)
Limited marketing information sometimes becomes an obstacle for farmers in marketing their products, so that farmers fail to get a fairer farmer share. This research was carried out by the survey method and aimed to determine the efficiency of the tuber marketing system by the community around the forest in Gunungkidul Regency, Yogyakarta. Data was collected by interviewing 31 tuber farmers selected by the purposive method and five traders selected by the snowball method. There are two tubers commodities, namely cassava, and cocoyam, that have been marketed by the community around the forest in fresh cassava, dry cassava, and fresh cocoyam. The tuber trading system was carried out through two trading system channels involving three intermediate traders, including village collectors, regency collectors, and retailers. Cassava trading arrangements are carried out through two trading channels are channel 1: farmers sell cassava to village collectors, who sell it to district collectors, then finally distribute it to the consumer. Channel 2: farmers sell fresh cassava to village collector, who sells it to regency collector (tapioca flour industry) and finally to consumers. While in cocoyam trading, two trading channels are also formed, among others. Channel 1: farmers sell fresh cocoyam to village collectors, then sell again to retailers who distribute it to consumers. Channel 2: the farmer sells fresh cocoyam directly to food processing producers than consumers. Cassava and cocoyam trading via channel 1 are more efficient than trading system two because they have a lower trading margin, greater farmers' share value, and less technical efficiency.